Assemblage characteristics of clay minerals and its implications to evolution of eolian dust input to the Parece Vela Basin since 1.95 Ma - 明洁 李安春 黄杰 万世明 孟庆勇 蒋富清 闫文文 (Chinese journal of oceanology and limnology, 2014)
To understand the provenance and evolution of eolian input in the last 1.95 Ma in the Parece Vela Basin in the eastern Philippine Sea, the clay mineral assemblage of a gravity core PV090510 from the basin was investigated using paleogeomagnetic dating and X-ray diffraction. The assemblage of the core mainly consisted of smectite (∼46%) and illite (∼40%), with some chlorite (∼10%) and kaolinite (∼4%). Analysis of the provenance of these minerals suggested that smectite was mainly derived from volcanic rocks of the Mariana Arc, while illite, chlorite, and kaolinite were mainly transported as eolian dust by the East Asian monsoon from central Asia. We used the ratio of (illite+chlorite+kaolinite)/smectite as a proxy for Asian eolian input to the Parece Vela Basin since 1.95 Ma. This ratio followed glacial and interglacial cycles and was consistent with the intensity of the East Asian monsoon and aridity of central Asia since 1.95 Ma. The changes of the ratio reflected three different stages of the East Asian monsoon and provenance climate.